Ziarah Menurut Agama Yahudi - Mohd. Khambali @ Hambali, Khadijah (Jurnal Usuluddin, 1996)
Ziyarah according to Jews Jurisprudence, is an act that involves elements of scarifying and sacramental aspects. In other word, ziyarah creates responsibilities and obedience among the Jewish for religious purpose. Thus, the idea of ziyarah has changed. It is only a remembrance of the past. Therefore, this article attempts to describe ziyarah according to Jewish belief.